3,6-dideoxy-3,6-imino-1,2-o-isopropylidene-α-d-glucofuranose as a divergent intermediate for the synthesis of hydroxylated pyrrolidines; synthesis of 1,4 dideoxy-1,4-imino-l-gulitol,... - Fleet, G; Peach, J; Smith, P; Austin, G; Baird, P; Watkin, D (1987)
Title full: 3,6-dideoxy-3,6-imino-1,2-o-isopropylidene-α-d-glucofuranose as a divergent intermediate for the synthesis of hydroxylated pyrrolidines; synthesis of 1,4 dideoxy-1,4-imino-l-gulitol, 1,4-dideoxy-i,4-imino-d-lyxitol, 2S,3S,4R-3,4-dihydroxyproline and (1S,2R,8S,8aR)-1,2,8-trihydroxyoctahydroindolizine [8-epi swainsonine]. X-ray crystal structure of (1S,2R,8S,8aR)-1,2,8-trihydroxy-5-oxo octahydroindolizine. An efficient synthesis of the p-toluenesulphonate salt of 3,6-dideoxy-3,6-imino 1,2-0-isopropylidene-α-D-glucofuranose (1) from glucose is reported; the potential of (1) in making hydroxylated pyrrolidines is illustrated by the preparation of 1,4-dideoxy-1,4-imino-L-gulitol, 1,4-dideoxy-1,4-imino-D-lyxitol (a powerful α galactosidase inhibitor), 2S,3S,4R-3,4-dihydroxyproline and (1S,2R,8S,8aR)-1,2,6 trihydroxyoctahydroindolizine [8-epi-Swainsonine]. An X-ray crystal structure of (1S,2R,83,8aR)-1,2,8-trihydroxy-5-oxo-octahydroindolizine is reported. © 1987.